An Efficient One‐Pot Four‐Segment Condensation Method for Protein Chemical Synthesis1. (13th March 2015) - Tang, Shan; Si, Yan‐Yan; Wang, Zhi‐Peng; Mei, Kun‐Rong; Chen, Xin; Cheng, Jing‐Yuan; Zheng, Ji‐Shen; Liu, Lei
Abstract Successive peptide ligation using a one‐pot method can improve the efficiency of protein chemical synthesis. Although one‐pot three‐segment ligation has enjoyed widespread application, a robust method for one‐pot four‐segment ligation had to date remained undeveloped. Herein we report a new one‐pot multisegment peptide ligation method that can be used to condense up to four segments with operational simplicity and high efficiency. Its practicality is demonstrated by the one‐pot four‐segment synthesis of a plant protein, crambin, and a human chemokine, hCCL21.